HISTOARCHITECTURE OF ADRENAL GLAND OF ADULT WHITE SWISS MICE - S. AL-Samarrae, N.; J. Al-Saffar , F. (The Iraqi Journal of Veterinary Medicine, 1990)
white swiss mice used to study the adrenal gland. These animals were anaesthetized, sacrificed, then samples of adrenal glands were collected and six micrometers thick sections were stained by both H & E and silver stains. Light microscopic observations showed that the glands are built up closely of packed cellular zone (glomerulosa); followed by a broader one (zona fasciculata) consist of cellular cords heavily loaded by lipid droplets. The later is followed by a zona reticularis, which is composed of anastomosed cellular cords, closely opposite to the wide sinusoids. The study showed fibrous line of demarcation, separating cortex from medulla. Medullary tissue examination revealed the presence of group of ganglion cells. Finally, it was found that zonation of cortical tissues are devoid of zona intermediata.